Weed management in Indian Agriculture: current scenario and way forward - Sharma, A. R.; Yaduraju, N. T.; Das, T. K. (Indian Farming, 2018)
Weed management in India is going on since 1952. The serious research in weed science was undertaken during 1970s when herbicides like 2,4 D, butachlor, isoproturon, atrazine were found highly effective in major cereal crops. This work was strengthened with the launching of All India Coordinated Research Project on Weed Control in 1978, and establishment of National Research Centre for Weed Science in 1989 at Jabalpur (renamed as Directorate of Weed Research in 2014). Globally, herbicides are the leading group of pesticides with 45% of the total consumption compared to a mere 18% in India. Wheat and rice account for major share of the total herbicide consumption in the country. At present 60 technical herbicides and 17 combination herbicides are registered for use in our country. However, indiscriminate use of herbicides has increased instances of herbicide resistance in weeds and occurrence of herbicide residue hazards. Herbicide-tolerant crops might become a reality in Indian agriculture after addressing some of the anticipated concerns. Changing climate is an issue which will intensify weed problems. An integrated and holistic approach with multi-disciplinary, multi-locational and multi-institutional involvement would be imperative to tackle future weed problems in India.